Gaming time and impulsivity as independent yet complementary predictors of gaming disorder risk - Paulina Daria Szyszka; Aleksandra Zajas; Jolanta Starosta; Patrycja Kiszka; Sylwia Starzec; Paweł Strojny (Scientific Reports)
Abstract Prolonged gaming time, along with increased impulsivity—a key element of poor self-regulation—has been identified as linked to gaming disorder. Despite existing studies in this field, the relationship between impulsivity and gaming time remains poorly understood. The present study explored the connections between impulsivity, measured both by self-report and behavioral assessments, gaming time and gaming disorder within a cohort of 82 participants. While gaming time exhibited a significant correlation with gaming disorder, only self-reported measures of impulsivity and one behavioral metric showed a correlation with gaming disorder. Self-report measures of impulsivity exclusively predicted gaming disorder when included in a regression model with gaming time. The interaction between gaming time and impulsivity, aside from one behavioral metric was deemed insignificant. These findings suggest that impulsivity and gaming time, although associated with gaming disorder risk, are independent variables. Further research should aim to clarify these relationships and explore potential interventions targeting both DGI and impulsivity to mitigate gaming disorder risk.